Magnetic polarized metal and preparation method and application thereof
By preparing Sr3Co2O7 single crystal thin film with layered perovskite structure, the difficulties of existing magnetic polarized metals in terms of metal compatibility, magnetism and polarization are solved, and the non-magnetic dependence abnormal Hall effect of long-range ordered magnetic and topological protection is realized, ensuring a stable information storage function.
Patent Information
- Application Number
- CN202311387760.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2025-04-29
AI Technical Summary
Existing magnetically polarized metals have difficulties in material design and preparation and internal mechanism complexity. They cannot be compatible with metallicity, magnetism and polarization at the same time, and the correlation between electrons and lattice is poor, so they cannot show stable topological magnetism and corresponding electromagnetic responses.
A single crystal thin film of Sr3Co2O7 with a layered perovskite structure was prepared, and by providing plasmas of A, B and oxygen, depositing and annealing at a set temperature to form a magnetic polarized metal with long-range ordered magnetism.
The high-quality Sr3Co2O7 single crystal thin film is prepared, with magnetic polarized metal properties, showing the non-magnetic dependence hall effect of topological protection, ensuring a stable information storage function, and having excellent structural integrity, metal conductivity and atomic polarization.
Smart Images

Figure CN119907620A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the research and development and preparation technology of new quantum information materials, especially a magnetic polarized metal and its preparation method and application. Background Art
[0002] The polarizability of materials is reflected in the directional movement of fixed atoms in the lattice, which destroys the spatial inversion symmetry of the crystal structure and derives a series of properties with application prospects and rich physical significance, such as ferroelectricity, multiferroicity, and anomalous energy level splitting. Among many polarized materials, magnetic polarized materials, as an emerging material, can not only achieve spontaneous polarization and electric potential dipole field, but also have excellent conductivity and magnetism. It is expected to further couple physical degrees of freedom such as charge, spin, orbit, and lattice, thus having the potential to become one of the important carriers of information, and therefore has attracted extensive attention and research.
[0003] In previous studies, the preparation and synthesis of polarized metals was a very severe challenge, and the introduction of magnetism was an insurmountable technical barrier. As a new type of information material, the research on magnetic polarized metals mainly faces two challenges: on the one hand, the difficulty in material design and preparation, which requires the simultaneous compatibility of metallicity, magnetism, and polarization; on the other hand, the complexity of the internal mechanism, which requires the creation of correlations between electrons and lattices and spins, thereby presenting stable topological magnetism and corresponding electromagnetic responses. However, the magnetic polarized metals reported so far cannot meet the requirements of the above challenges very well, for example, they do not have long-range ordered magnetism, and the correlation between electrons and lattices is poor. Summary of the invention
[0004] The following is an overview of the subject matter described in detail herein. This overview is not intended to limit the scope of protection of this application.
[0005] The present application provides a magnetic polarized metal, the chemical formula of which is A3B2O a , the main element at the A position is Sr, the main element at the B position is Co, O is oxygen, and a is in the range of 6 to 7.3.
[0006] In an embodiment of the present application, the magnetic polarized metal may be Sr3Co2O7.
[0007] In an embodiment of the present application, the A position may further include a first doping element, and the first doping element may be selected from any one or more of alkaline earth metal elements and lanthanide elements.
[0008] In an embodiment of the present application, the alkaline earth metal elements may include Be, Mg, Ca, Sr and Ba, and the lanthanide elements may include La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu.
[0009] In an embodiment of the present application, the B site may further include a second doping element, and the second doping element may be selected from any one or more transition metal elements.
[0010] In an embodiment of the present application, the transition metal elements may include Co, Cr, Fe, Mn, Ni, Cu, Ti, Zn, Sc and V.
[0011] In an embodiment of the present application, the magnetically polarized metal has a layered perovskite structure.
[0012] In an embodiment of the present application, the magnetic polarization metal is a single crystal thin film.
[0013] In an embodiment of the present application, the basic structural unit of the single crystal film can be composed of a double perovskite layer 2×SrCoO3 and an adjacent rock salt layer SrO, wherein Co in one perovskite layer is a polarized atom and Co in another perovskite layer is a non-polarized atom.
[0014] In the embodiment of the present application, the resistivity of the magnetic polarized metal between -271.15°C and 130°C is 10 2 On the order of μΩcm.
[0015] The present application also provides a method for preparing the magnetic polarized metal as described above, the manufacturing method comprising:
[0016] providing plasma of A, B and oxygen;
[0017] In a first oxygen-containing gas atmosphere, the plasma of A, B and oxygen is deposited on a substrate at a set temperature to form an intermediate product A3B2O 7-x A film of, wherein x is an oxygen-deficient concentration stoichiometric ratio, and x is in the range of 0 to 1;
[0018] In a second oxygen-containing gas atmosphere, the A3B2O 7-x The film is annealed to make the intermediate product A3B2O 7-x Converted into A3B2O7, the magnetically polarized metal is obtained.
[0019] In an embodiment of the present application, the plasma providing A, B and oxygen may include:
[0020] A reactant containing element A, element B and element oxygen is used as a precursor, and under the bombardment of a pulsed laser, the element A, element B and element oxygen in the precursor are converted into plasma.
[0021] In an embodiment of the present application, the precursor containing the A element, the B element, and the oxygen element may be a ceramic containing the Sr element and the Co element.
[0022] In an embodiment of the present application, the first oxygen-containing gas may be oxygen gas, and the pressure of the first oxygen-containing gas may be 10 mTorr to 30 mTorr.
[0023] In an embodiment of the present application, the second oxygen-containing gas may be ozone.
[0024] In an embodiment of the present application, the deposition method may be an epitaxial deposition method.
[0025] In an embodiment of the present application, the set temperature may be 600°C to 800°C.
[0026] In an embodiment of the present application, the material of the substrate may be (LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 or SrTiO3.
[0027] In an embodiment of the present application, the annealing temperature may be 200°C to 400°C.
[0028] In an embodiment of the present application, the preparation method may further include: in forming the intermediate product A3B2O 7-x Thereafter, before providing the second oxygen-containing gas,
[0029] In the intermediate product A3B2O 7-x A protective layer is deposited on the thin film, and the material of the protective layer is DyScO3.
[0030] The embodiment of the present application further provides a nonvolatile magnetic memory, the nonvolatile magnetic memory comprising a magnetic storage unit, the magnetic storage unit comprising the magnetic polarization metal provided in the embodiment of the present application.
[0031] The embodiment of the present application also provides a solid fuel cell cathode material, and the solid fuel cell cathode material includes the magnetic polarized metal provided in the embodiment of the present application.
[0032] This application prepared high-quality Sr3Co2O7 single crystal thin film for the first time, and confirmed that it has magnetic polarization metal properties and can be used as a magnetic polarization material; it was found that the transition metal ion polarization shift in the material is 11.6pm, which is comparable to the atomic polarization shift of traditional ferroelectric materials such as BaTiO3. In addition, based on the results of electromagnetic transport, we discovered a topologically protected non-magnetic dependent anomalous Hall effect (AHE) loop. This non-magnetic dependent AHE loop can ensure a stable information storage function without the influence of out-of-plane magnetic moment and its demagnetization field, providing an ideal carrier for future small-size information storage and manipulation.
[0033] The magnetically polarized metal of the embodiment of the present application has excellent structural integrity, metallic conductivity, room temperature magnetism, atomic polarizability, and very strong non-volatile information storage function.
[0034] Other features and advantages of the present application will be described in the following description, and partly become apparent from the description, or be understood by implementing the present application. Other advantages of the present application can be realized and obtained by the schemes described in the description and the drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The accompanying drawings are used to provide an understanding of the technical solution of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the technical solution of the present application and do not constitute a limitation on the technical solution of the present application.
[0036] Figure 1 A process flow chart of a method for preparing a magnetic polarized metal provided for an exemplary embodiment of the present application;
[0037] Figure 2 The Sr3Co2O obtained by the method for preparing magnetic polarized metal according to the exemplary embodiment of the present application 7-x Schematic diagram of the film structure;
[0038] Figure 3 A schematic diagram of the structure of a Sr3Co2O7 film obtained by the method for preparing a magnetic polarized metal according to an exemplary embodiment of the present application;
[0039] Figure 4 The X-ray diffraction pattern of the Sr3Co2O7 film prepared in Example 1 of the present application;
[0040] Figure 5 This is an atomic resolution image of the Sr3Co2O7 thin film prepared in Example 1 of the present application in a high-angle annular dark field image mode of a scanning transmission electron microscope;
[0041] Figure 6This is a graph showing the atomic displacement characterization results of the Sr3Co2O7 thin film prepared in Example 1 of the present application in the annular bright field image mode of a scanning transmission electron microscope;
[0042] Figure 7 This is a diagram showing the quantitative statistical results of atomic polarization of the Sr3Co2O7 film obtained in Example 1 of the present application;
[0043] Figure 8 Sr3Co2O prepared in Example 1 of the present application 7-x The resistivity curve of Sr3Co2O7 film changes with temperature;
[0044] Fig. 9 Sr3Co2O prepared in Example 1 of the present application 7-x and the hysteresis loop of Sr3Co2O7 thin film;
[0045] Fig.10 Sr3Co2O prepared in Example 1 of the present application 7-x and X-ray absorption spectra of Sr3Co2O7 thin films and X-ray magnetic circular dichroism absorption spectra of Sr3Co2O7 and SrCoO3;
[0046] Fig.11 Abnormal Hall effect curves of the Sr3Co2O7 film prepared in Example 1 of the present application at different temperatures;
[0047] Fig.12 The anomalous Hall effect curve and hysteresis loop of the Sr3Co2O7 film prepared in Example 1 of the present application at 25K;
[0048] Fig.13 for Fig.12 The numerical and geometric dissection results of the hysteresis loop;
[0049] Fig.14 The loop amplitude of the anomalous Hall effect curve of the Sr3Co2O7 film prepared in Example 1 of the present application;
[0050] Fig.15 The curve showing the change of the Hall coefficient of the Sr3Co2O7 film obtained in Example 1 of the present application with temperature;
[0051] Fig.16 Schematic diagram of the non-magnetic dependent constant Hall effect curve loop of the Sr3Co2O7 film prepared in Example 1 of the present application and the corresponding flipping mechanism under a magnetic field. DETAILED DESCRIPTION
[0052] The present application describes multiple embodiments, but the description is exemplary rather than restrictive, and it is obvious to those skilled in the art that there may be more embodiments and implementations within the scope of the embodiments described in the present application. Although many possible feature combinations are shown in the drawings and discussed in the specific embodiments, many other combinations of the disclosed features are also possible. Unless specifically limited, any feature or element of any embodiment may be used in combination with any other feature or element in any other embodiment, or may replace any other feature or element in any other embodiment.
[0053] The present application includes and contemplates combinations of features and elements known to those of ordinary skill in the art. The embodiments, features and elements disclosed in the present application may also be combined with any conventional features or elements to form a unique invention scheme defined by the claims. Any features or elements of any embodiment may also be combined with features or elements from other invention schemes to form another unique invention scheme defined by the claims. Therefore, it should be understood that any feature shown and / or discussed in the present application may be implemented individually or in any appropriate combination. Therefore, except for the limitations made according to the attached claims and their equivalents, the embodiments are not subject to other restrictions. In addition, various modifications and changes may be made within the scope of protection of the attached claims.
[0054] In addition, when describing representative embodiments, the specification may have presented the method and / or process as a specific sequence of steps. However, to the extent that the method or process does not rely on the specific order of the steps described herein, the method or process should not be limited to the steps of the specific order described. As will be understood by those of ordinary skill in the art, other sequences of steps are also possible. Therefore, the specific sequence of the steps set forth in the specification should not be interpreted as a limitation to the claims. In addition, the claims for the method and / or process should not be limited to the steps of performing them in the order written, and those skilled in the art can easily understand that these sequences can be changed and still remain within the spirit and scope of the embodiments of the present application.
[0055] The intrinsic polarized metals reported so far are mainly divided into three types, namely torsional, ferroelectric, and interface types. Among them, torsional polarized metals mainly appear in oxide systems, and their atomic polarization is mainly driven by the rotation of oxygen octahedrons; ferroelectric polarized metals mainly exist in van der Waals layered materials, and the polarization is mainly reflected in the different inversion environments between adjacent layers; the atomic polarization of interface polarized metals mainly exists at the interface, and its driving force mainly comes from the difference in the electric potential environment of adjacent layers. Unfortunately, the polarized metals reported so far do not have long-range ordered magnetism, so it is difficult to reflect the existence and transmission of this new quantum state in electromagnetic transport. For this reason, the design and preparation of new magnetic polarized metals with long-range ordered magnetism has become a highly anticipated scientific vision.
[0056] In addition, in addition to the difficulty in possessing long-range ordered magnetism, the above-mentioned intrinsic polarized metals also have the following problems: torsional polarized metals mainly appear in oxide systems, and their atomic polarization is mainly driven by the rotation of oxygen octahedrons. Their shortcoming is that the coupling between free electrons and the lattice is weak, and it is difficult to exhibit electronic correlation properties; ferroelectric polarized metals mainly exist in van der Waals layered materials, which require very strict control of the number of layers and complex sample transfer technology, and are therefore difficult to use for large-area integration; the atomic polarization of interface polarized metals mainly exists at the interface, and this localized polarization method is difficult to achieve broad electronic correlation characteristics, which is not conducive to carrying quantum information states.
[0057] The present application provides a magnetic polarized metal, the chemical formula of which is A3B2O a , the main element at the A position is Sr, the main element at the B position is Co, O is oxygen, and a is in the range of 6 to 7.3.
[0058] In the embodiments of the present application, a may be 6, 6.5, 7 or 7.3, etc.
[0059] In an embodiment of the present application, the magnetic polarized metal may be Sr3Co2O7.
[0060] In an embodiment of the present application, the A position may also include a first doping element, that is, the main element of the A position may be "partially" replaced by the first doping element, thereby forming an element-doped magnetic polarized metal; the first doping element may be selected from any one or more of alkaline earth metal elements and lanthanide elements.
[0061] In an embodiment of the present application, the alkaline earth metal elements may include beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba), and the lanthanide elements may include lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu).
[0062] In an embodiment of the present application, the B position may further include a second doping element, that is, the main element of the B position may be "partially" replaced by the second doping element; the second doping element may be selected from any one or more transition metal elements.
[0063] In an embodiment of the present application, the transition metal elements may include cobalt (Co), chromium (Cr), iron (Fe), manganese (Mn), nickel (Ni), copper (Cu), titanium (Ti), zinc (Zn), scandium (Sc) and vanadium (V).
[0064] In an embodiment of the present application, the magnetically polarized metal has a layered perovskite structure.
[0065] In an embodiment of the present application, the magnetic polarization metal is a single crystal thin film.
[0066] In an embodiment of the present application, the basic structural unit of the single crystal film can be composed of a double perovskite layer 2×SrCoO3 and an adjacent rock salt layer SrO, wherein Co in one perovskite layer is a polarized atom and Co in another perovskite layer is a non-polarized atom.
[0067] In the embodiment of the present application, the resistivity of the magnetic polarized metal between -271.15°C and 130°C is 10 2 The resistivity is in the order of μΩcm, showing typical metallic resistivity behavior.
[0068] The embodiment of the present application also provides a method for preparing the magnetic polarized metal as described above. Figure 1 A process flow chart of a method for preparing a magnetic polarized metal provided for an exemplary embodiment of the present application.
[0069] like Figure 1 As shown, the preparation method comprises:
[0070] providing plasma of A, B and oxygen;
[0071] In a first oxygen-containing gas atmosphere, the plasma of A, B and oxygen is deposited on a substrate at a set temperature to form an intermediate product A3B2O 7-x A film of, wherein x is an oxygen-deficient concentration stoichiometric ratio, and x is in the range of 0 to 1;
[0072] In a second oxygen-containing gas atmosphere, the A3B2O 7-x The film is annealed to make the intermediate product A3B2O 7-x Converted into A3B2O7, the magnetically polarized metal is obtained.
[0073] In an embodiment of the present application, the plasma providing A, B and oxygen may include:
[0074] A reactant containing element A, element B and element oxygen is used as a precursor, and under the bombardment of a pulsed laser, the element A, element B and element oxygen in the precursor are converted into plasma.
[0075] In an embodiment of the present application, the precursor containing the A element, the B element, and the oxygen element may be a ceramic containing the Sr element and the Co element.
[0076] In an embodiment of the present application, the first oxygen-containing gas may be oxygen.
[0077] In an embodiment of the present application, the pressure of the first oxygen-containing gas can be 10mTorr to 30mTorr, for example, it can be 10mTorr, 11mTorr, 12mTorr, 13mTorr, 14mTorr, 15mTorr, 16mTorr, 17mTorr, 18mTorr, 19mTorr, 20mTorr, 21mTorr, 22mTorr, 23mTorr, 24mTorr, 25mTorr, 26mTorr, 27mTorr, 28mTorr, 29mTorr or 30mTorr.
[0078] In an embodiment of the present application, the second oxygen-containing gas may be ozone.
[0079] In an embodiment of the present application, the deposition method may be selected from any one or more of pulsed laser deposition and epitaxial deposition.
[0080] In an embodiment of the present application, the set temperature may be 600°C to 800°C, for example, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C or 800°C.
[0081] In an embodiment of the present application, the substrate may be an epitaxial substrate formed of strontium tantalum lanthanum aluminate.
[0082] In an embodiment of the present application, the material of the substrate may be (LaAlO3)0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 (LSAT for short). Alternatively, other cubic, tetragonal and orthorhombic structure substrates may be used, for example, SrTiO3.
[0083] In an embodiment of the present application, the deposition method may be an epitaxial deposition method, for example, pulsed laser deposition (PLD) may be used to perform deposition on an epitaxial substrate.
[0084] In an embodiment of the present application, the annealing temperature may be 200°C to 400°C, for example, 200°C, 210°C, 220°C, 230°C, 240°C, 250°C, 260°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C.
[0085] In an embodiment of the present application, the preparation method may further include: forming the intermediate product A3B2O 7-x Afterwards, before providing the second oxygen-containing gas, the intermediate product A3B2O 7-x A protective layer is formed on the film.
[0086] The protective layer may be any stable air isolation layer for isolating water vapor in a humid environment. For example, the material of the protective layer may be DyScO3.
[0087] In an exemplary embodiment of the present application, the preparation method may include:
[0088] (LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 The substrate is placed flat on the heating table of the pulsed laser deposition system as an epitaxial substrate, and the temperature is set to 600℃ to 800℃, and the oxygen pressure is 10mTorr to 30mTorr. Then the pulsed laser is turned on to bombard the target (ceramic containing Sr and Co elements), and the volatilized Sr, Co, and O plasma are epitaxially deposited on the substrate to form the oxygen-deficient phase Sr3Co2O 7-x The oxygen vacancies in the film are mainly located between the two perovskite layers, such as Figure 2 As shown, and in Sr3Co2O 7-x The film surface is covered with a layer of DyScO3 as a protective layer. Then, ozone is introduced at 200°C to 400°C for annealing to obtain the following Figure 3 The Sr3Co2O7 thin film is shown.
[0089] like Figure 2 and Figure 3 As shown, Sr3Co2O 7-x The basic structural unit of the film and Sr3Co2O7 film is composed of a double perovskite layer 2×SrCoO3 and an adjacent rock salt layer SrO. Figure 3 As shown, the polarization of Co atoms exists in one of the perovskite layers, while the Co atoms in the other layer are non-polarized atoms.
[0090] The embodiment of the present application further provides a nonvolatile magnetic memory, the nonvolatile magnetic memory comprising a magnetic storage unit, the magnetic storage unit comprising the magnetic polarization metal provided in the embodiment of the present application.
[0091] The embodiment of the present application also provides a solid fuel cell cathode material, and the solid fuel cell cathode material includes the magnetic polarized metal provided in the embodiment of the present application.
[0092] The magnetic polarization metal provided in the embodiment of the present application is an oxide having a layered perovskite structure, and the resistivity is maintained at 10 2 It is on the order of μΩ.cm and therefore has good electronic and ionic conductivity, as well as oxygen catalytic activity, and can be used as a cathode material for solid-state fuel cells.
[0093] Example 1
[0094] (LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 The substrate (LSAT for short) is placed flat on the heating table of the pulsed laser deposition system as an epitaxial substrate, and the temperature is set to 750°C and the oxygen pressure is 15mTorr. Then the pulsed laser is turned on to bombard the ceramic containing Sr and Co elements. The volatilized Sr, Co, and O plasma are epitaxially deposited on the LSAT substrate to form the oxygen-deficient phase Sr3Co2O 7-x The oxygen vacancies in the film are mainly located between the two perovskite layers and in the Sr3Co2O 7-x The surface of the film is covered with a layer of DyScO3 as a protective layer. Then, ozone is introduced at 300°C for annealing to obtain a Sr3Co2O7 film.
[0095] The structure of the prepared Sr3Co2O7 film was characterized by X-ray diffraction (XRD) and scanning transmission electron microscopy (STEM). Figure 4 and Figure 5 As shown. Among them, Figure 4The X-ray diffraction pattern of the Sr3Co2O7 film prepared in Example 1 of the present application; Figure 5 This is an atomic resolution image of the Sr3Co2O7 thin film prepared in Example 1 of the present application in the high-angle annular dark field (HAADF) mode of a scanning transmission electron microscope.
[0096] Figure 4 The XRD curve shows five characteristic peaks of (002), (004), (006), (008) and (0010), which proves that the Sr3Co2O7 prepared in the embodiment of the present application has excellent single crystal properties.
[0097] from Figure 5 It can be seen that the Sr3Co2O7 film and the LSAT substrate have a crystal coherence relationship in the
[001] direction, and the entire material presents a nearly perfect structural integrity, with clear occupancy of Sr and Co atoms, as shown in Figure 3 The structural diagram is shown in FIG.
[0098] Figure 6 This is an enlarged atomic structure diagram of the Sr3Co2O7 film obtained in the annular bright field (ABF) mode of the scanning transmission electron microscope of the embodiment 1 of the present application, which is used to characterize and quantify the atomic displacement in the Sr3Co2O7 film obtained in the embodiment 1 of the present application. Figure 6 It can be seen that there is a unidirectional Co atom displacement in Sr3Co2O7 along the
[001] direction.
[0099] Figure 7 This is a quantitative statistical result diagram of atomic polarization of the Sr3Co2O7 film obtained in Example 1 of the present application. Figure 7 It can be seen that in the perovskite double layer, the polarization displacement of the upper Co atoms (L1 layer) is 11.6pm, while the lower Co atoms (L2 layer) have basically no polarization displacement. The crystal structure is just as Figure 3 As shown in the figure, the material breaks the mirror symmetry of the (001) plane, and the material shows a macroscopic spatial inversion symmetry breaking.
[0100] In order to further characterize the physical properties of the material, we first tested the Sr3Co2O prepared in Example 1 of this application on a comprehensive physical property measurement platform. 7-x The resistivity curve of Sr3Co2O7 film changes with temperature, such as Figure 8 As shown. Among them, Sr3Co2O 7-x The resistivity of 8 μΩ.cm, showing the characteristics of an insulator; while the resistivity of Sr3Co2O7 remains at 10 2 The μΩ.cm level is within the range of common metal materials.
[0101] In addition, we tested the Sr3Co2O prepared in Example 1 of this application. 7-x The hysteresis loop of Sr3Co2O7 film, such as Fig. 9 As shown. Fig. 9 We can find that Sr3Co2O7 exhibits long-range ordered magnetism, and the magnetic easy axis is biased towards the in-plane direction. 7-x It does not reflect long-range ordered magnetism, so the hysteresis loop is not obvious.
[0102] We then conducted a series of X-ray absorption and X-ray magnetic circular dichroism absorption characterization experiments to trace the origin of its magnetism, such as Fig.10 In the X-ray absorption spectrum, we compared Sr3Co2O7 and Sr3Co2O 7-x The spectral lines of Co and their L3 characteristic peaks were found to be around 780 eV, proving that Co mainly exists in the +4 valence state (abbreviated as Co 4+ ). However, the oxygen-deficient phase Sr3Co2O 7-x The characteristic peak of L3 shows a red shift of 0.5 eV, which indicates that Sr3Co2O 7-x The presence of a small amount of +3-valent Co in Sr3Co2O7 further confirms the high-quality structure and chemical order of Sr3Co2O7. 4+ The magnetic moment analysis was performed and the results of Sr3Co2O7 and SrCoO3 were compared. It was found that although the magnetic properties of both materials are determined by Co 4+ contribution, the magnetic moment of SrCoO3 will be greater than that of Sr3Co2O7, which also means that Co in Sr3Co2O7 4 +'s electron orbital occupancy state is more complex than that in traditional SrCoO3, and is also expected to contain richer physical properties.
[0103] So far, we have proved that Sr3Co2O7 has metallic properties, atomic polarizability, and long-range ordered magnetism. Next, we conducted anomalous Hall measurements on the material on a comprehensive physical property measurement platform. The test results are as follows: Figures 11 to 15 shown.
[0104] like Fig.11 As shown in the figure, the signal of the anomalous Hall effect (AHE) appears at room temperature 300K, indicating that ordered magnetism is established at this temperature. When the temperature is further reduced to below 200K, the signal of the AHE gradually shows an abnormal shape change.
[0105] by Fig.12 Taking the data of 25K as an example, the hysteresis loop σ in the out-of-plane direction s Compared with M, the AHE curve σ in magnetic polarized metals xyIt presents a square loop and has a large coercive field (y=0) and residual value (x=0), which also shows that the Sr3Co2O7 film prepared in Example 1 of the present application has a very strong non-volatile information storage function.
[0106] In addition, we found that the AHE loop can be split into two parts, such as Fig.13 As shown, the magnetically dependent σ1 and the non-magnetically dependent σ2, and each of them changes with temperature to form Fig.14 Gradient curve shown.
[0107] Combination Fig.15 The temperature-dependent Hall coefficient of the Sr3Co2O7 film obtained in Example 1 of the present application shows the change in carrier type. We can further know that this temperature-dependent AHE comes from the topologically protected Bailey curvature (Ω xy ) is the contribution of the AHE loop. The non-magnetic AHE loop can be further attributed to the vertical Née state pseudovector derived from the polarization breaking. It has little contribution to magnetism, but in the polarization field and magnetic field The real space can be flipped under the joint action of Fig.16 In addition, since the out-of-plane residual net magnetic moment is too small or even disappears, this non-magnetic-dependent AHE caused by spatial symmetry breaking has a more stable information storage performance than the traditional magnetic-dependent AHE.
[0108] In summary, the magnetically polarized metal of the embodiment of the present application has excellent structural integrity, metallic conductivity, room temperature magnetism, atomic polarizability, and very strong non-volatile information storage function.
[0109] Although the implementation methods disclosed in this application are as above, the contents described are only implementation methods adopted to facilitate understanding of this application, and are not intended to limit this application. Any technician in the field to which this application belongs can make any modifications and changes in the form and details of implementation without departing from the spirit and scope disclosed in this application, but the scope of patent protection of this application shall still be defined by the attached claims.
Claims
1. A magnetically polarized metal, characterized in that: The chemical formula is A3B2O a , the main element at the A position is Sr, the main element at the B position is Co, O is oxygen, and a is in the range of 6 to 7.
3.
2. The magnetically polarized metal according to claim 1, characterized in that: It is Sr3Co2O7.
3. The magnetically polarized metal according to claim 1, characterized in that: The A site further includes a first doping element, and the first doping element is selected from any one or more of alkaline earth metal elements and lanthanide elements.
4. The magnetically polarized metal according to claim 3, characterized in that: The alkaline earth metal elements include Be, Mg, Ca, Sr and Ba, and the lanthanide elements include La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb and Lu.
5. The magnetically polarized metal according to claim 3, characterized in that: The B site further includes a second doping element, and the second doping element is selected from any one or more transition metal elements.
6. The magnetically polarized metal according to claim 5, characterized in that: The transition metal elements include Co, Cr, Fe, Mn, Ni, Cu, Ti, Zn, Sc and V.
7. The magnetically polarized metal according to any one of claims 1 to 6, characterized in that It has a layered perovskite structure.
8. The magnetically polarized metal according to any one of claims 1 to 6, characterized in that: It is a single crystal thin film.
9. The magnetically polarized metal according to claim 8, characterized in that: The basic structural unit of the single crystal film is composed of a double perovskite layer 2×SrCoO3 and an adjacent rock salt layer SrO, wherein Co in one perovskite layer is a polarized atom and Co in another perovskite layer is a non-polarized atom.
10. The magnetically polarizable metal according to any one of claims 1 to 9, characterized in that: The resistivity is 10 between -271.15℃ and 130℃ 2 On the order of μΩcm.
11. A method for preparing a magnetically polarizable metal according to any one of claims 1 to 10, characterized in that: include: providing plasma of A, B and oxygen; In a first oxygen-containing gas atmosphere, the plasma of A, B and oxygen is deposited on a substrate at a set temperature to form an intermediate product A3B2O 7-x A film of, wherein x is an oxygen-deficient concentration stoichiometric ratio, and x is in the range of 0 to 1; In a second oxygen-containing gas atmosphere, the A3B2O 7-x The film is annealed to make the intermediate product A3B2O 7-x Converted into A3B2O7, the magnetically polarized metal is obtained.
12. The preparation method according to claim 11, characterized in that: The plasma providing A, B and oxygen comprises: Using a reactant containing element A, element B, and element oxygen as a precursor, and converting the element A, element B, and element oxygen in the precursor into plasma under the bombardment of a pulsed laser; Wherein, the precursor containing element A, element B and element oxygen is a ceramic containing element Sr and element Co; The first oxygen-containing gas is oxygen, and the pressure of the first oxygen-containing gas is 10 mTorr to 30 mTorr; The second oxygen-containing gas is ozone.
13. The preparation method according to claim 11, characterized in that: The deposition method is epitaxial deposition; The set temperature is 600°C to 800°C.
14. The preparation method according to claim 11, characterized in that: The material of the substrate is (LaAlO3) 0.3 -(SrAl 0.5 Ta 0.5 O3) 0.7 or SrTiO3.
15. The preparation method according to claim 11, characterized in that: The annealing temperature is 200°C to 400°C.
16. The preparation method according to any one of claims 11 to 15, characterized in that: Also includes: In forming the intermediate product A3B2O 7-x Thereafter, before providing the second oxygen-containing gas, In the intermediate product A3B2O 7-x A protective layer is deposited on the thin film, and the material of the protective layer is DyScO3.
17. A non-volatile magnetic memory, characterized in that: A magnetic storage unit is included, the magnetic storage unit comprising the magnetically polarized metal according to any one of claims 1 to 10.
18. A solid fuel cell cathode material, characterized in that: Comprising the magnetically polarizable metal according to any one of claims 1 to 10.